الرقابة القضائية على القرارات الإدارية الضمنية -دراسة مقارنة- - فاكية خلوط; لطيفة خلوط (My University, 2023)
Research Summary : The administrative authority carries out several activities through the means it owns, represented in the legal acts issued by the administration and administrative decisions, which are one of the important privileges of the administration, and therefore the administration must issue these decisions in the form specified by the law. However, when the administration exaggerated in not responding to the requests and grievances of its clients, which resulted in depriving them of their rights and freedoms, based on this situation, the need arose to control the incident of silence in the field of administrative decisions, which led to the emergence of implicit administrative decisions. This is what led to the imposition of judicial oversight on the actions of the administrative authority to ensure that it is issued in accordance with the principle of legality, by means of judicial oversight represented in the abolition of decisions that violate the law, and the provision of appropriate compensation to individuals who have suffered damage as a result of its application. Accordingly, judicial oversight is the most important oversight that can guarantee the rule of the principle of legality. ................................................ ملخص البحث باللغة العربية تمارس السلطة الإداریـــة عـــدة أنشطة بواسطة ما تملكه مـــن وسائـــل تتمثــل فـــي الأعمـــال القانونیـــة التـــي تصدرها الإدارة و كالقرارات الإداریة و التي تعد أحد الإمتيازات الهامة للإدارة، و لذلك فإنـــه یتعیـــن علــى الإدارة أن تقوم بإصدار هذه القرارات في الشكل الذي حدده لها القانون . إلا أنه عندما بالغت الإدارة في عدم ردها على طلبات وتظلمات المتعاملين معها، الأمر الذي نتــج عنـــه حرمانهم من حقوقهم وحرياتهم، فانطلاقا من هذا الوضع ظهرت الحاجـــة إلـــى ضبــط واقعــة السكـــوت فـــي مجال القرارت الإدارية ، الأمر الذي أدى إلى نشوء القرارات الإدارية الضمنية. هذه الأخيرة تستوجب تسليط رقابــة قضائیـة عليهــا للتــأكد مــن صدورهـــا وفقــــا لمبـــدأ المشروعیة بواسطة وسائـــل الرقابــــة القضائيــــة المتمثلـــة فــي إلغـــاء القـــرارات المخالفــــة للقانـــون ، والحكــــم بالتعویـــض المناســب للأفراد الذین أصابهم الضرر نتیجة لتطبیقها. وعليه فإن الرقابة القضائیة هي أهم رقابة یمكن أن تضمن سیادة مبدأ المشروعیة وإحترام حقوق الأفراد. .......................................... باللغـــة الأنجليزيـــة: Research Summary : The administrative authority carries out several activities through the means it owns, represented in the legal acts issued by the administration and administrative decisions, which are one of the important privileges of the administration, and therefore the administration must issue these decisions in the form specified by the law. However, when the administration exaggerated in not responding to the requests and grievances of its clients, which resulted in depriving them of their rights and freedoms, based on this situation, the need arose to control the incident of silence in the field of administrative decisions, which led to the emergence of implicit administrative decisions. This is what led to the imposition of judicial oversight on the actions of the administrative authority to ensure that it is issued in accordance with the principle of legality, by means of judicial oversight represented in the abolition of decisions that violate the law, and the provision of appropriate compensation to individuals who have suffered damage as a result of its application. Accordingly, judicial oversight is the most important oversight that can guarantee the rule of the principle of legality.